A comparison between the balance method and radiotracer methods for measuring calcium absorption in treated and untreated patients with osteoporosis - Reeve, J; Bijvoet, O; Neer, R; Slovik, D; Tellez, M; Vismans, F; Zanelli, G (1980)
Measurements of calcium absorption by the balance method and by the double tracer, multiple blood sampling radiocalcium tracer method were synchronized in 48 studies in 35 patients with osteoporosis. In the patients who were studied twice, results were obtained before and during treatment. Significant correlations were obtained between fractional dietary calcium absorption and three measures of the rate of 47Ca absorption : the maximum rate of absorption (M.A.R.) and mean rate of absorption (AR), both calculated by deconvolution analysis from the results of the double tracer study ; and the mean rate of absorption calculated from the oral tracer appearance curve using Marshall and Nordin's (1969) method (L.A.R.). None of these correlations were sufficiently good for the radiocalcium absorption test to be able to replace the expensive and time-consuming balance technique in the detailed study of absorption of calcium from the diet or calcium balance in individual patients with osteoporosis. Only a small part of this lack of correspondence could be accounted for by methodological uncertainties. The most sensitive radiocalcium absorption tests appear to be those which measure rates of absorption and they appear best suited to studying patients in homogeneous groups rather than individually. © 1980.